Efforts to Improve the Quality of Learning of the Qur’an and Hadith Through the Takrir Method - Suryanti, Eti; Herlina, N. Hani; Endang, Ujang (Graduate Program, Darussalam Institut for Islamic Studies, 2018)
The Takrir method is believed to have a number of advantages in developing students' abilities in studying the Qur'an and the Sunnah of the Prophet. The classroom action research conducted at the Ibtidaiyah Rijalul Hikam Jatinegara Madrasah in Ciamis Regency successfully proved that the takrir method was effective in al-Qu'an and Sunnah Nabi learning.